Hadith as Scripture: Discussions on the Authority of Prophetic Traditions in Islam by Aisha Y. Musa (New York: Palgrave and Macmillan, 2008. 224 pages.) (American Journal of Islam and Society, 2010)
This book treats the debate among Muslims over the authority of hadith,which by the ninth century had been raised to the level of scripture. Theauthor’s main purpose is to show that modern Muslim thinkers who question its status as a source of law are not the first ones to do so and thus cannot bedismissed as inauthentic aberrations or the results of a western, colonialistplot to undermine Islam. In addition, modern arguments against this viewhave close parallels in the opinions attributed to those of their predecessors.Hadith as Scripture thus has a strong presentist concern, despite its treatmentof classical Islamic sources, and can be seen as apologetic in that it seeks todefend the Qur’an-only position from unfair detraction ...